Falencia del servicio al cliente en la Empresa KTM sport de la ciudad de Vinces en el periodo 2022. - Palacios Gavilanes, Amy Sully (2023)
The research seeks to identify the causes of the problems related to the failure in the quality of customer service in the company KTM Sport in the city of Vinces in the period 2022, and to propose effective solutions to improve customer satisfaction and strengthen the company's image in the market. For this purpose, qualitative and quantitative methods of information collection will be used, theoretical and practical knowledge related to customer service, quality management and marketing will be integrated, and skills such as the ability to analyze, synthesize and propose effective solutions will be put into practice. The purpose of this research is to analyze the causes and consequences of the failure in the quality of customer service in the company KTM Sport in the city of Vinces in the period 2022, in order to propose effective solutions to improve customer satisfaction and strengthen the company's image in the market. This case study is justified because it will help improve customer relations, allowing the company to offer exceptional service. This increases customer satisfaction and loyalty, which in turn contributes to increased sales, profits and a better company image. Good customer service can also save time and resources by improving organizational efficiency. Qualitative and quantitative data collection methods will be used to conduct this research, such as customer interviews, satisfaction surveys, direct observation of customer service, review of company documents and records, among others. Based on the data collected, a detailed and rigorous analysis will be carried out to identify the causes of the problem and propose concrete solutions.